Pemberdayaan Masyarakat Desa Tepas Melalui Transformasi Basmitah Berkah - Andi Maria Ulfa; Ariesta Ramdhani; Jamiatul Aulia; Sahratullah; seprianingsih, dewi (Jurnal Pengabdian Magister Pendidikan IPA, 2024)
This study focuses on the empowerment of the Tepas Village community through the transformation of Basmitah Berkah, a community-based initiative aimed at improving local economic conditions. The initiative integrates modern agricultural practices with local wisdom, promoting sustainable development and enhancing community welfare. The program includes training, capacity building, and resource management aimed at fostering independence and resilience within the community. The outcomes demonstrate increased economic activity, better resource management, and improved social cohesion